2020
DOI: 10.1002/ldr.3758
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial and fungal communities and associated nutrient cycling in relation to rice cultivation history after reclamation of natural wetland

Abstract: The reclamation and utilization of natural wetlands can affect the community structure of soil microorganisms. However, knowledge regarding succession of microbial communities during long‐term reclamation and the links with related nutrient cycles is still limited. Using Illumina sequencing, we identified the patterns and environmental drivers of soil bacterial and fungal succession along a 150‐year chronosequence of paddy fields. Soil enzyme activities were determined to characterize functions related to C, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…These results together indicate that fungal succession was faster than bacterial succession and that fungi could form a new stable community more quickly after long‐term rice cultivation. Much evidence of different response patterns in fungi and bacteria to environmental changes has been reported (Feng et al, 2019; Hu et al, 2021), and some studies have observed competitive relationships between fungi and bacteria (Bell et al, 2014; Rousk et al, 2008). A previous study focusing on the effects of drought on soil microbial networks found that drought promotes destabilizing properties in bacterial networks, whereas fungal networks show higher stability (de Vries et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These results together indicate that fungal succession was faster than bacterial succession and that fungi could form a new stable community more quickly after long‐term rice cultivation. Much evidence of different response patterns in fungi and bacteria to environmental changes has been reported (Feng et al, 2019; Hu et al, 2021), and some studies have observed competitive relationships between fungi and bacteria (Bell et al, 2014; Rousk et al, 2008). A previous study focusing on the effects of drought on soil microbial networks found that drought promotes destabilizing properties in bacterial networks, whereas fungal networks show higher stability (de Vries et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microorganisms are critical factors that influence soil aggregation and aggregate stability due to their biomass, community structure, and metabolic products ( Six et al, 2004 ; Rashid et al, 2016 ). According to the conceptual model of Golchin et al (1994) , fresh and labile organic matter favors microorganism growth, thereby stimulating the soil microbiota, increasing soil microbial activities, and promoting the stability of soil aggregates ( Guo et al, 2020 ; Hu et al, 2020 ). On the one hand, afforestation induces increase in fresh organic material from litter input, root biomass, and exudates ( Lan, 2020 ; Lan et al, 2022 ), thus promoting SOC and liable OC accumulation ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further study is needed to clarify how changes in certain bacterial taxa at different classification levels effectively explain the changes in SOC fractions. According to the conceptual model of Golchin et al (1994) , fresh and labile organic matter increased the availability of organic matter, thereby promoting microorganism growth; this phenomenon causes rapid stimulation of soil microbiota, increases soil microbial activities, and enhances soil aggregation and soil aggregate stability ( Guo et al, 2020 ; Hu et al, 2020 ). Changes in soil aggregate stability were closely associated with soil bacterial community ( Rahman et al, 2017 ; Zhao et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…PNR was measured as described by Qian et al (2017) . The activity of soil enzymes was assayed using the protocol according to Hu et al (2021) . In brief, four hydrolases (Bglu, Bxyl, NAG, Phos) were assayed using 4-methylumbelliferyl (MUB) as substrate, and two oxidases (Poxi and Pero) were determined using 3, 4-dihydroxy-L-phenylalanine (L-DOPA) as substrate.…”
Section: Methodsmentioning
confidence: 99%